NONCONVENTIONAL TECHNIQUE FOR PREPARING COMPRESSION-PROOF CELLULAR GLASS (Nonconventional Technologies Review, 2023)
Producing foamed bottle type with excellent heat-insulating features (denseness within the limits of  0.30-0.45 g·cm-3, heat conduction in the range of 0.064-0.093 W·m-1·K-1, and porousness within the limits of 78.6-85.7 %), and simultaneously high compression properties (6.3-8.2 MPa) was achieved in economical and environmentally friendly conditions using nonconventional method of preponderantly direct electromagnetic wave warming. The material mixture was composed of recycled residual coloured glass, CaCO3, borax, glycerin, water glass, and water adding. The sintering/expanding temperature had values between 829-845 ℃. Due to the high energy effectiveness of the warming technique designed by authors, the warming rate had excellent values (18.8-23.8 ℃/min) without affecting the quality of cellular bottle specimens and the electricity consumption was reduced (0.83-1.06 kWh/kg).
Keywords: cellular bottle; direct microwave warming; residual bottle; borax; glycerin; water glass